Physical growth of students aged 10 to 14 on Santa Catarina island - Ruy Jornada Krebs; Zenite Machado (Universidade Federal de Santa Catarina, 2001)
The purpose of this study was to verify, by means of socioeconomic and cultural indicators, the profile of development and physical growth of students aged from 10 to 14, both native and non-native to Florianópolis, Santa Catarina Island, state of Santa Catarina, Brazil, and to investigate whether natives differ from non-natives. The casual comparative method (Gay, 1987) was employed and supplemented with the person-context paradigm (Bronfenbrenner, 1991). The study enrolled 365 students of both sexes: 265 of them natives and 100 non-natives. Physical growth was assessed in terms of body weight and height, with the NCHS curves as reference standard. Data were analyzed by means of descriptive statistics, the chi-square test, Student's t test of Student and Pearson's correlation coef. cient. The results show that locals have greater body weight than non-locals and that both groups exhibit lower weight than the NCHS standard values. Values for height were also greatest on the NCHS scale, followed by natives and then non-natives. It was observed that the macrosystem of Santa Catarina Island, analyzed in the light of socio-economic and cultural indicators, is homogeneous for the students that were analyzed here and is therefore able to have the same influence on their development profiles. We may add that this influence on the students is positive. RESUMO O objetivo deste estudo foi verificar a partir de indicadores sócioeconômicos e culturais como se apresenta o macrossistema Ilha de Santa Catarina, como se caracteriza o crescimento físico dos escolares de 10 a 14 anos, naturais e não naturais de Florianópolis e, se existe diferença entre os nativos comparados com os não nativos. Valendo-se do método causal-comparativo (Gay, 1987) e suportando-se no paradigma pessoa-contexto (Bronfenbrenner, 1991), o estudo teve, como sujeitos, 365 escolares de ambos os sexos, (265 nativos e 100 não nativos). O crescimento físico foi avaliado por meio do peso e altura corporais tendo como padrão de referência o do NCHS. A análise dos dados procedeu-se através da estatística descritiva, teste quiquadrado, teste "t" de Student e correlação de Pearson. Quanto aos resultados verificou-se que os escolares naturais de Florianópolis apresentam valores para peso superiores aos dos não naturais e, ambos, inferiores aos do padrão de referência do NCHS. Os valores do padrão de referência mostraram-se superiores também na variável altura corporal sendo seguidos pelos dos escolares não nativos e, após, pelos dos nativos. Observo-use ainda que o macrossistema Ilha de Santa Catarina, interpretado através de indicadores socioeconômicos e culturais, mostrou-se homogêneo para os escolares investigados tornando-o, passível, portanto, de exercer igual influência sobre seus perfis de desenvolvimento. Acrescenta-se que esta influência apresentou-se, entre eles, como positiva.